Pengaruh Perubahan Dividen Terhadap Profitabilitas Perusahaan Pada Masa Yang Aakan Datang (Future Profitability) - Agus Prasetyanta (Jurnal Ekonomi dan Bisnis, 2014)
The research investigates the incremental information content of dividend changes about future profitability. We regress three of measurement of earnings (earnings level, earnings changes and abnormal earnings) to dividend changes and a number of control variables. By using 87 samples (420 firm years) of firm at Jakarta Stock Exchange over 1997-2003, We find that dividend changes provide information about the earnings insubsequent years, incremental to market and accounting data. The paper also documents that dividend changes are positively related to earnings changes for merely four year ahead. In detail examining, We find that dividend increase convey must new information about earnings changes and abnormal earnings for three year ahead than dividend decrease.